Ataxia-Telangiectasia Mutated Modulation of Carbon Metabolism in Cancer - Dahl, Erika S.; Aird, Katherine M. (Frontiers in Oncology, 2017)
The ataxia-telangiectasia mutated (ATM) protein kinase has been extensively studied for its role in the DNA damage response and its association with the disease ataxia telangiectasia. There is increasing evidence that ATM also plays an important role in other cellular processes, including carbon metabolism. Carbon metabolism is highly dysregulated in cancer due to the increased need for cellular biomass. A number of recent studies report a non-canonical role for ATM in the regulation of carbon metabolism. This review highlights what is currently known about ATM’s regulation of carbon metabolism, the implication of these pathways in cancer, and the development of ATM inhibitors as therapeutic strategies for cancer.